DESIGN OF MEASURING INSTRUMENT OF GLUCOSE CONCENTRATION IN SOLUTION USING NEAR-INFRARED SPECTROSCOPY (NIRS) METHOD - Sanjaya, Christian
Diabetes mellitus is a long-term disease resulting from disturbances in insulin secretion. Based on data from the Ministry of Health, Indonesia is ranked seventh out of ten countries with the highest number of people with diabetes mellitus worldwide. These data show that one of the leading causes of the increasing number of people with diabetes mellitus in Indonesia is the consumption pattern of people who like to consume sweet drinks. As many as 61.3% of respondents stated that the frequency of consuming sweet beverages in one day was more than once. Through the Ministry of Health, the Indonesian government recommended a daily sugar intake limit of 50 g/ml. In contrast(Johnson dkk., 2009), the average sugar content in packaged drinks is 20 grams per serving. The consumption pattern of sugary beverages needs to be controlled to reduce risk factors for diabetes by limiting daily sugar intake. Therefore we need a hardware device to measure glucose levels in the solution. One method to measure the level of glucose concentration in a solution is by using the near-infrared spectroscopy (NIRS) method. The simple working principle of NIRS is to measure the absorption rate of the sample.